The cost dynamics of hydrogen supply in future energy systems – A techno-economic study - Öberg, Simon; Odenberger, Mikael; Johnsson, Filip (Applied energy, 2022)
[Display omitted] •The cost dynamics of hydrogen supply in future energy systems is investigated.•The cost of hydrogen influenced by several factors, in addition to electricity cost.•The hydrogen demand profile has a considerable impact on cost of hydrogen.•Flexibility in the hydrogen demand can reduce the cost by more than 30%.•Time-shifting of electricity generation via hydrogen provides a system value. This work aims to investigate the time-resolved cost of electrolytic hydrogen in a future climate-neutral electricity system with high shares of variable renewable electricity generation in which hydrogen is used in the industry and transport sectors, as well as for time-shifting electricity generation. The work applies a techno-economic optimization model, which incorporates both exogenous (industry and transport) and endogenous (time-shifting of electricity generation) hydrogen demands, to elucidate the parameters that affect the cost of hydrogen. The results highlight that several parameters influence the cost of hydrogen. The strongest influential parameter is the cost of electricity. Also important are cost-optimal dimensioning of the electrolyzer and hydrogen storage capacities, as these capacities during certain periods limit hydrogen production, thereby setting the marginal cost of hydrogen. Another decisive factor is the nature of the hydrogen demand, whereby flexibility in the hydrogen demand can reduce the cost of supplying hydrogen, given that the demand can be shifted in time. In addition, the modeling shows that time-shifting electricity generation via hydrogen production, with subsequent reconversion back to electricity, plays an important in the climate-neutral electricity system investigated, decreasing the average electricity cost by 2%–16%. Furthermore, as expected, the results show that the cost of hydrogen from an off-grid, island-mode-operated industry is more expensive than the cost of hydrogen from all scenarios with a fully interconnected electricity system.